Methods of Radiation Wavelength Tuning in Short-Pulsed Fibre Lasers - Sergey Kobtsev (Photonics, 2023)
Methods of output wavelength tuning in short-pulsed fibre lasers are analysed. Many of them rely on spectral selection principles long used in other types of lasers. For compatibility with the fibre-optical format, the corresponding elements are sealed in compact, airtight volumes with fibre-optical radiation input and output. A conclusion is presented about the relatively small number of inherently “fibre-optical” ways of tuning the wavelength of radiation. It is demonstrated that the range of output wavelength tuning in short-pulsed fibre lasers may span hundreds of nanometres (even without extension beyond the active medium gain contour through nonlinear effects). From the presented review results, it may be concluded that the search for the optimal tuning method complying with the user-preferred all-PM-fibre short-pulsed laser design is not yet complete.